Applied psychology in talent management - Cascio, Wayne F. 1946-; Aguinis, Herman 1966- (SAGE, 2019)
NEW TO THIS EDITION: Offers the most up-to-date coverage of technological and demographic trends changing the nature of work and organizations worldwide. Seamless application of concepts with the inclusion of action-oriented learning objectives allows students to understand the most important state-of-the-science talent management issues. Incorporates evidence-based guidelines for practice, allowing students to learn through research and apply the concepts. New topics to the Eighth Edition include the impact of globalization and the digital revolution on product and service markets, as well as demographic changes on labor markets, approaches to managing talent, and the composition of organizations; recruitment as one element of a talent supply chain; and implementing new techniques in HR management such as agile management, use of artificial intelligence, and analytics to improve the overall recruitment process. KEY FEATURES: Integrates psychological theory with tools and methods for dealing with human resource problems in organizations and for making organizations more effective, satisfying places to work. Reflects the state-of-the-art in talent management and outlines a forward-looking, progressive model toward which HR specialists should aim. Provides students with a comprehensive and practical approach that challenges the field to advance, rather than to simply document past practice. Enables students to apply psychological research and theory to human resource management in organizations. A broader performance management emphasis provides students with a more proactive approach when looking at behavioral and judgmental biases in rating, types of performance measures, and performance feedback.